Serbia Public Finance Review : Toward a Sustainable and Efficient Fiscal Policy - World Bank Group (World Bank, Washington, DC, 2015)
Since the global economic and financial crisis of 2008, Serbia has struggled with a weak economy and a deteriorating fiscal position. Until 2008, fiscal deficits were moderate and public debt declined significantly. Since the start of the global economic and financial crisis in 2008, however, Serbia has struggled with the interlinked problems of minimal growth and unfavorable fiscal dynamics. As economic activity has stagnated, revenues have fallen and expenditures, particularly mandatory spending on pensions and wages, have remained high. At the same time, structural fiscal issues, such as continued state support to state-owned enterprises (SOEs) and tax administration inefficiencies, have been a drag on growth. As a result of these pressures, general government fiscal deficits averaged 5.6 percent of GDP a year between 2009 and 2014. Reflecting the high fiscal deficits and poor economic growth, Serbia’s public debt has more than doubled, from 34 percent of GDP in 2008 to 71 percent at yearend-2014. The objective of this report is therefore two-fold: (i) policy options and recommendations (beyond those built into the current program) that would help solidify the ongoing fiscal consolidation program and help achieve public debt sustainability over the medium term; and (ii) given near-term fiscal constraints, identify opportunities for enhancing the efficiency, quality, and equity of current public spending on health, education, and social protection over the medium term